Analisis Nilai Sosial dan Nilai Moral Pada Novel Pulang Karya Leila S. Chudori Serta Pemanfaatannya sebagai Bahan Ajar Sastra Indonesia di SMK At Taubah Batubantar - Gunawan, Abdurofi (Jurnal Artikula, 2025)
Analysis of Social Values and Moral Values in the Novel Pulang by Leila S. Chudori and Its Utilization as Teaching Material at SMK At Taubah. The novel Pulang by Leila S. Chudori is rich in representations of social and moral life, an in-depth study of the values contained therein, especially in the context of its relevance as teaching material. This is because instilling character and moral values in students, especially at the vocational school level, is a crucial aspect in the formation of a complete personality. Therefore, this study aims to describe Social Values and Moral Values, This type of research is qualitative with a descriptive method. The object of this research is a novel book entitled "Pulang" by Leila S.Chudori. The data collection technique used is the data analysis technique using descriptive analysis, observation, marking, interpreting, describing, and recording. After conducting the research, the researcher found 19 Social Values data including Discipline 3 data, Tolerance 4 data, Empathy 4 data, Hard Work 4 data, Social Care 4. And 18 Moral Values data, including Human Relationships with God 6 data, Human Relationships with Themselves 5 data, Human Relationships with Other Humans in the Social Scope 7 data. This analysis of Social Values and Moral Values can be used as Indonesian Language teaching materials at SMK At Taubah Batubantar